FORMATION OF A MARKETING COMPLEX FOR SMALL BUSINESS IN SOCIAL NETWORKS - Kosar, N.S.; Podaryn , V.R. (The actual problems of regional economy development, 2022)
The existing concepts for the formation of the marketing complex of the enterprise are well researched, but the modification of business, the development of the e-commerce market and changes in consumer behavior necessitate clarification, further research on this concept, including adaptation to business digitalization. An important aspect of today is the growth of entrepreneurship in social networks, especially small businesses. The online activity of such enterprises has certain features that significantly influence the development of their marketing mix. Therefore, the aim of the article is to study the peculiarities of the formation of a marketing complex for small businesses in social networks. In the process of writing such methods as analysis, synthesis, systematization, comparison, induction, deduction, abstract-logical and graphic were used. The approaches of domestic scientists to the definition of the essence of the marketing complex are given, on the basis of which the definition of the marketing complex of the subject of entrepreneurial activity in social networks is formed. The evolutionary development of the most popular concepts for the formation of the marketing complex of the enterprise is analyzed, the analysis of which allowed to identify the main categories (product policy, pricing policy, distribution policy and promotion policy) namely: “4P”, “4C” and “SIVA”. The combination of these concepts in the context of marketing interaction and communication, as well as a certain interaction of their elements, leads to the union of ”roducer complex” and “consumer complex”. The characteristics of the digital consumer in social networks, the features of doing business of small businesses on this platform, which directly affect the formation of their marketing mix. The scheme of a complex of digital marketing in social networks for small business is offered, stages of process of its development are resulted. It is determined that in order to form a complex of marketing of a business entity in social networks it is necessary to use a combination of several concepts, as none of them is exhaustive and complete to achieve the goals of modern business transformation and digitalization. The practical value of the results of the study is that they determine the main elements that should be taken into account by the subjects when conducting activities in social networks.